Análise de pontos iniciais em métodos de pontos interiores para o problema de pré-despacho - Mota, Gabriela (Universidade Federal de São Carlos, 2022)
Due to the complexity of the Brazilian electrical system, it is necessary to apply methods that minimize losses in all generation and transmission stages, including the predispatch of the system. The resolution of these problems using interior point methods is widely used, due to its robustness and speed. The choice of the efficient initial point is of great importance, since it influences the number of iterations and the computational time. In this work, sought to compare the computational time and number of iterations in the resolution of predispatch problem by the primal-dual interior point path-follower method with starting point of Mehrotra and the starting point obtained from the midpoint of the constraints. From the results obtained, it can be concluded that the starting point proposed by Mehrotra has an advantage in the amount of iterations, however no advantage was observed in the computational time.
Starting point analysis in interior point methods for the predispatch problem
Keywords: Ponto inicial; Métodos de pontos interiores; Pré-despacho; Initial point; Interior point methods; Predispatch problem; ENGENHARIAS::ENGENHARIA DE PRODUCAO::PESQUISA OPERACIONAL::PROGRAMACAO LINEAR, NAO-LINEAR, MISTA E DINAMICA